2021
DOI: 10.1111/jocn.16003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nurse‐led care on fatigue in patients with rheumatoid arthritis: A systematic review and meta‐analysis of randomised controlled studies

Abstract: Aims and objectives This study aimed to investigate the effect of nurse‐led care on fatigue in patients with rheumatoid arthritis. Background Evaluating the effect of nurse‐led care on fatigue in patients with rheumatoid arthritis will be useful in planning appropriate nursing interventions to increase the functional status and quality of life of patients. Design Systematic review and meta‐analysis. Methods A comprehensive literature review was conducted on the Cochrane Library, Web of Science, PubMed, EBSCOho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Although classical CBT interventions have been found to be useful in the past, effect sizes are relatively small and considered unsatisfactory [ 26 , 27 , 61 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although classical CBT interventions have been found to be useful in the past, effect sizes are relatively small and considered unsatisfactory [ 26 , 27 , 61 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that there was no discernible difference in disease activity after one year between the nurse-led follow-up and the conventional physician-led monitoring. The findings of a meta-analysis indicated that the nurse-led approach was beneficial for managing fatigue [ 18 ].…”
Section: Nurses Involvement In the Management Of Rheumatic Diseasesmentioning
confidence: 99%
“…The systematic literature shows that tracker-based interventions increase physical activity alone or combined [ 336 ]. Indeed, wearing a tracker is considered an intervention and an increased motivation by information and peer mentoring [ 337 ].…”
Section: New Applicationsmentioning
confidence: 99%